Pediatric Tuberculosis Management: A Global Challenge or Breakthrough? - Lehlogonolo N. F. Maphalle; Bozena B. Michniak-Kohn; Modupe O. Ogunrombi; Oluwatoyin A. Adeleke (MDPI AG, 2022)
Managing pediatric tuberculosis (TB) remains a public health problem requiring urgent and long-lasting solutions as TB is one of the top ten causes of ill health and death in children as well as adolescents universally. Minors are particularly susceptible to this severe illness that can be fatal post-infection or even serve as reservoirs for future disease outbreaks. However, pediatric TB is the least prioritized in most health programs and optimal infection/disease control has been quite neglected for this specialized patient category, as most scientific and clinical research efforts focus on developing novel management strategies for adults. Moreover, the ongoing coronavirus pandemic has meaningfully hindered the gains and progress achieved with TB prophylaxis, therapy, diagnosis, and global eradication goals for all affected persons of varying age bands. Thus, the opening of novel research activities and opportunities that can provide more insight and create new knowledge specifically geared towards managing TB disease in this specialized group will significantly improve their well-being and longevity.